Extracellular matrix stiffness in endometrial cancer: driving progression and modulating treatment sensitivity via the ROCK1/YAP1 axis - Rui Sun; Ying Zhao; Yao Liu; Mengyao Zhang; Ziyi Qiu; Xiaohong Ma; Lina Wei; Wei Lu; Zhiming Liu; Jie Jiang (Cell Death and Disease)
Abstract Endometrial cancer (EC) is among the most prevalent gynecological malignancies, with advanced or recurrent cases posing significant treatment challenges due to limited responses to conventional therapies. Growing evidence highlights the critical role of extracellular matrix (ECM) stiffness in driving tumor progression by shaping the tumor microenvironment. In this study, we demonstrate that ECM stiffness is significantly higher in EC tissues compared to normal endometrium, correlating with elevated expression of ROCK1, a mechanosensitive kinase. Using atomic force microscopy (AFM), we quantified ECM stiffness, while polyacrylamide gels with varying stiffness were employed to mimic ECM conditions in vitro. Bioinformatics analyses, immunofluorescence, Western blotting, and co-immunoprecipitation experiments revealed that ROCK1 modulates the phosphorylation of YAP1, promoting its nuclear localization and transcriptional activity, thereby driving aggressive tumor behaviors, including enhanced proliferation, migration, invasion, and reduced apoptosis. Pharmacological inhibition of ROCK1 with Y-27632 mitigated these effects, suppressing tumor growth, restoring apoptosis, and inducing cell cycle arrest. Treatment with Y-27632 improved sensitivity to chemotherapy and radiotherapy, and significantly enhanced macrophage-mediated phagocytosis, thereby boosting anti-tumor immune responses. In hormone-resistant EC cells, ROCK1 inhibition restored sensitivity to progesterone therapy. Notably, in vivo experiments in a xenograft mouse model confirmed the therapeutic potential of Y-27632, as combination therapy with progesterone showed superior tumor-suppressive effects compared to monotherapy. These findings underscore the dual role of ECM stiffness and ROCK1 in driving tumor progression and influencing treatment outcomes. By elucidating the relationship between ECM stiffness, ROCK1/YAP1 signaling, and treatment sensitivity, this study highlights the potential of targeting the ROCK1/YAP1 axis as a therapeutic strategy. ROCK1 serves as both a biomarker for prognosis and a target for improving personalized treatment approaches, offering new avenues to enhance clinical outcomes for EC patients.